Cost-efficiency of cross-taxon surrogates in temperate forests. (April 2018) - Larrieu, Laurent; Gosselin, Frédéric; Archaux, Frédéric; Chevalier, Richard; Corriol, Gilles; Dauffy-Richard, Emmanuelle; Deconchat, Marc; Gosselin, Marion; Ladet, Sylvie; Savoie, Jean-Marie; Tillon, Laurent; Bouget, Christophe
Highlights: No single taxon was firmly identified as a relevant surrogate for other taxa. Forest species exhibited a lower surrogacy than the taxon as a whole. Using a set of two or three taxa drastically increased surrogacy. Four categories of taxa were delineated based on cost-efficiency scores. Abstract: Cross-taxon surrogacy (between-taxon similarities in species patterns) can help conservation biologists to design simplified, standardized and efficient tools for biodiversity monitoring. Our study aims to identify potential sets of indicator taxa to be recommended in temperate forests. We focused on nine forest taxa: vascular plants, bryophytes, saproxylic beetles, polypores, lichens, ground beetles, hoverflies, birds and bats. We assessed cross-taxon congruence patterns, in terms of both alpha and beta-diversity, using empirical biodiversity data from 206 plots in ten French forested areas. We evaluated the cost-efficiency of potential surrogate taxa using both strictly encoded expert knowledge and results of this study. The most congruent taxa in alpha-diversity were bryophytes (with bats and polypores), and ground beetles (with bats and saproxylic beetles), though levels of covariation were mostly weak. The most congruent taxon in beta-diversity was vascular plants (with bryophytes, ground beetles, lichens and forest birds). Contrary to our expectations, the subsets of forest species within a given taxon exhibited a lower surrogacy than the taxon as a whole. Four categories of taxa were delineated based on cost-efficiency scores – from costless but ineffective (bats and ground beetles) to costly but effective (saproxylic beetles and polypores). No single taxon was firmly identified as a relevant surrogate for other taxa; using a set of two or three taxa drastically increased surrogacy, compared with single-taxon approaches. Saproxylic beetles associated with vascular plants, or with both vascular plants and birds, seemed to be the most cost-efficient associations. Further research is required to up-scale our results from the short-term, local scale to the long-term, landscape scale in European temperate forests.